Effect of acidic environment on dislocation resistance of endosequence root repair material and mineral trioxide aggregate. - Noushin Shokouhinejad; Kazem Ashofteh Yazdi; Mohammad Hossein Nekoofar; Shakiba Matmir; Mehrfam Khoshkhounejad (Tehran University of Medical Sciences, 2014)
The aim of this study was to compare the effect of an acidic environment on dislocation resistance (push-out bond strength) of EndoSequence Root Repair Material (ERRM putty and ERRM paste), a new bioceramic-based material, to that of mineral tri-oxide aggregate (MTA).One-hundred twenty root dentin slices with standardized canal spaces were divided into 6 groups (n = 20 each) and filled with tooth-colored ProRoot MTA (groups 1 and 2), ERRM putty (groups 3 and 4), or ERRM paste (groups 5 and 6). The specimens of groups 1, 3, and 5 were exposed to phosphate buffered saline (PBS) solution (pH=7.4) and those of groups 2, 4, and 6 were exposed to butyric acid (pH= 4.4). The specimens were then incubated for 4 days at 37°C. The push-out bond strength was then measured using a universal testing machine. Failure modes after the push-out test were examined under a light microscope at ×40 magnification. The data for dislocation resistance were analyzed using the t-test and one-way analysis of variance.In PBS environment (pH=7.4), there were no significant differences among materials (P=0.30); but the mean push-out bond strength of ERRM putty was significantly higher than that of other materials in an acidic environment (P